Insect biodiversity of boreal peat bogs - Spitzer, Karel; Danks, Hugh V (Annual review of entomology, 2006)
Boreal peat bogs contain distinctive insects in addition to widely distributed generalists, including species restricted to bogs (tyrphobionts) and species characteristic of bogs but not confined to them (tyrphophiles). Bogs raised above the water table form characteristic habitat islands in southern boreal and temperate forest zones. Many bogs have persisted for hundreds and even thousands of years, preserving relict ecosystems related to subarctic biomes. The historical development and nature of individual bogs are reflected by differences among their insects, which are of great biogeographical and ecological interest. The environmental sensitivity of bogs also makes insects valuable as bioindicators. Moreover, few readily accessible bogs remain in a natural state. Given the scientific interest of bog insects and the fact that each relict bog habitat island is unique, further studies of the diversity of bog faunas are merited, and the conservation of these habitats should be strongly supported by entomologists.
Keywords: životní prostředí; Insecta; genetická variace; Environment; Genetic Variation; Canada; Animals; půda; Kanada; Soil; hmyz; biodiverzita; zachování přírodních zdrojů; zvířata; Conservation of Natural Resources; Evropa; Europe; Biodiversity